reastfeeding Experience of Women of High Socioeconomic Status: A Phenomenological Study - Berbano, Audrey Ysabelle S.; Ordanozo, Ally Shawnae I.; Lalatag, Isabelle Rae O.; Bingcang, Angel Grace Fio; Obon, April Marqueses (11th International Scholars Conference, 2018)
Studies on the implications brought about socioeconomic and breastfeeding practices is not sufficiently explored in the Philippines. The aim of the study is to explore the breastfeeding experiences among Filipino women with high socioeconomic status, as well as their needs in order to initiate and continue breastfeeding. The study utilized qualitative research methods. Six respondents participated in the study and were selected using snowball sampling. A semi-structured interview was done to obtain relevant information about the study. Colaizzi’s method was used to analyze the collected data. The emergent themes developed as follows: (1) perceptions of mothers about breastfeeding, (2) breastfeeding experience of mothers, and (3) needs of the mothers in order to breastfeed successfully. All mothers found breastfeeding to be difficult, most thought that it is best for infants and mothers. All mothers planned to breastfed antenatally and had to balance employment and breastfeeding. Most of them received support from their families, others from breastfeeding support groups, and workplaces. All mothers highlighted the importance of breastfeeding education for mothers, families, and health workers. They all found that determination and family support are significant for mothers to accomplish her desired breastfeeding goals. The researchers recommended that future studies should look into the specific knowledge deficiency of mothers, particularly those of high socioeconomic status regarding breastfeeding; development an extensive breastfeeding education program for health care professionals, pregnant and breastfeeding women, and family members.